2022
DOI: 10.1109/tpwrs.2022.3173160
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent Circuit Model of Grid-Forming Converters With Circular Current Limiter for Transient Stability Analysis

Abstract: This letter develops an equivalent circuit model of a grid-forming (GFM) converter with a circular current limiter and analyzes its transient stability. It is revealed that the inner control loop can be simplified as a voltage source behind an equivalent resistor. Based on the developed model, theoretical analysis and experimental tests demonstrate that the transient stability of a P − f droop-controlled GFM converter with the circular current limiter can be assured whenever there exist stable equilibrium poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…During normal operation, the output of the voltage integrator is close to zero in the steady-state since it is merely used to remove the impact of modeling errors [30]. Therefore, once the current limiter is triggered, the voltage integrator is kept at zero to avoid its windup [23].…”
Section: B Control Structurementioning
confidence: 99%
See 2 more Smart Citations
“…During normal operation, the output of the voltage integrator is close to zero in the steady-state since it is merely used to remove the impact of modeling errors [30]. Therefore, once the current limiter is triggered, the voltage integrator is kept at zero to avoid its windup [23].…”
Section: B Control Structurementioning
confidence: 99%
“…In [22], a theoretical approach is proposed to explain the post-fault behavior of GFM inverters with virtual impedance. Further, Fan et al [23] demonstrated the fault recovery process of GFM inverters with circular current limiters based on an equivalent circuit model. In [24], [25], transient instability induced by daxis priority-based current limiters when faults are cleared is revealed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation tests of the magnitude limiter and the prioritybased limiter with 𝜙 𝐼 = 0 are conducted to demonstrate their performance during severe symmetrical disturbances. The control structures in [19], [51] are utilized. During the disturbances, the power references are adjusted according to (5).…”
Section: E Case Studymentioning
confidence: 99%
“…In addition to the commonly used methods, such as back-calculation, clamping, etc., novel anti-windup algorithms for different current-limiting controls may be developed to help GFM inverters recover from the undesired current saturation. For example, in [51], the integrator of the voltage vector controller is set to zero when the current magnitude limiter is triggered to improve the fault recovery capability of the GFM inverter. In [76], [82], the outer-loop controllers are re-designed for prioritybased current limiters to avoid the windup of the voltage vector controller.…”
Section: Windup Of Voltage Controllersmentioning
confidence: 99%